Deciphering the dynamics of enzymes associated with the synthesis of cryoprotectants during cold acclimation in contrasting chickpea genotypes - Deeksha Padhiar; Sarbjeet Kaur; Anju Rani; Uday Chand Jha; P. V. Vara Prasad; Kamal Dev Sharma; Sanjeev Kumar; Swarup Kumar Parida; Kadambot H. M. Siddique; Harsh Nayyar (Scientific Reports)
Abstract Chickpea, a vital legume crop, is highly susceptible to cold stress, especially during its reproductive phase, resulting in significant flower and pod abortions and reduced seed yield. Our previous study demonstrated that cold acclimation is effective in enhancing cold tolerance but benefits only cold-tolerant (CT) genotypes, while cold-sensitive (CS) genotypes remain unaffected. In this extended study aimed at probing the detailed mechanisms of this differential response, we further examined the expression profiles of enzymes involved in the synthesis and breakdown of osmolytes (pyrroline-5-carboxylate synthase, proline dehydrogenase (PDH), betaine aldehyde dehydrogenase) and sugars (sucrose synthase, acid invertase, trehalose-6-phosphate synthase, trehalose-6-phosphate phosphatase, and trehalase activity), along with the expression of various antioxidants (superoxide dismutase, catalase, ascorbate peroxidase, and glutathione reductase) in both CT and CS genotypes. Seeds of two contrasting chickpea genotypes, cold-tolerant ICC 17258 and cold-sensitive ICC 15567, were planted in pots during the first week of November in an outdoor field environment. After 40 days, the plants were transferred to walk-in growth chambers for cold acclimation at specific temperatures. Initially, the plants were exposed the plants to 25/18℃ (pre-acclimation stage; PAS) for 2 days, followed by a 21-day cold acclimation period with progressively decreasing temperatures over seven days for each cold acclimation stage (CAS): CAS1 (21/13℃), CAS2 (18/10℃), and CAS3 (15/8℃). Subsequently, the plants were subjected to cold stress at 13/7℃ for 15 days and then exposed to 30/23℃ (12 h day/night) until maturity. Our findings demonstrated that the expression of various enzymes involved in the synthesis of osmolytes and sugars in leaves, anthers, and ovules was significantly upregulated during the cold acclimation process in the CT chickpea genotypes but not in the CS genotypes. This enhanced metabolic activity, coupled with elevated levels of enzymatic antioxidants during the acclimation process, contributed to improved leaf water status, photosynthetic efficiency, and ultimately, superior reproductive performance (pollen germination, pollen viability, stigma receptivity, and ovule viability) under cold stress conditions compared to CS genotypes. The enhanced cold tolerance observed in the CT genotypes is likely attributable to their genetic predisposition and efficient stress defense mechanisms facilitated by the upregulated expression of cold-responsive enzymes.